HADITH IN DIGITAL SPACE: AN INITIAL MAPPING - Nadjib, Ala'i; Firdausy, Hilmy; Umam, Khaerul (Peminat Ilmu Ushuluddin, 2024)
The development of the digital world and the proliferation of virtual spaces now occupy almost half in a day. In 2024, more than 65% of the Indonesian population will be connected to the internet and accessing various social media platforms. Every day, more than three hours of their time will be spent accessing information in the virtual world. This reality has changed many things, including the way people access, understand and practice religious information, including the Prophetic traditions. Therefore, various researches and studies have been conducted to observe this new phenomenon. This study will generally capture the extent to which research and studies on the circulation of Prophetic traditions in the digital space have been conducted. Using the systematic literature review technique, this article will map the development of the discourse, the variety of dissemination, and the map of studies that have been conducted with regard to hadith in the digital space. By observing all studies that focus on digital media platforms, this article finds that the development of hadith discourse in the digital world only grew exponentially in 2021 and was dominated by the discourse of authority and reception.